Making Linux work - Arman Danesh (Jamsa Press ; Albany, N.Y. : Onword Press, 2002)
Making Linux Work is the perfect desktop reference for the system administrator who has limited experience with Red Hat Linux and/or UNIX-based operating systems in general. Each section of the book begins with a fast-paced, 5-10 page overview of a specific topic that is followed directly by a collection of expertly categorized, thoroughly indexed tips and techniques. Tips are presented in a unique question-and-answer format, allowing even new Linux users to locate mission-critical information "on demand," drill down to essential details quickly, and make Linux work. Written by a SAIR Linux and GNU Certified Administrator, this invaluable reference contains everything needed to achieve proficiency in system installation; management of files, directories and disks; use and configuration of the Linux X Window System environment; and more! Its unique format is further guaranteed to increase the productivity of beginning through intermediate Red Hat Linux users by eliminating the need to wade through dense prose, extrapolate information from cookbook-style tutorials, struggle through complex tech docs, or engage in time-intensive, trial-and-error experimentation